anonymous
  • anonymous
iif cosectheta-cottheta=1\2 then costheta=?
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
welshfella
  • welshfella
I'll use O for theta:- csc O - cot O = 1/2 what is cos O you might do it this way csc^2 O = 1 + cot^2 O so substituting ; sqrt( 1 + cot^2 O) + cot O = 1/2 solve for cot O then you can find cos O using other trig identities
welshfella
  • welshfella
* typo in line 6 it should be sqrt( 1 + cot^2 O) - cot O = 1/2
welshfella
  • welshfella
you can also find the value of angle O from cot O then find cos O

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

welshfella
  • welshfella
I'll start the solution of the equation for you sqrt( 1 + cot^2 O) + cot O = 1/2 sqrt( 1 + cot^2 O) = cot O + 1/2 square both sides;- 1 + cot^2 O = cot^2 O + cot O + 1/4 now finding cot O is straightforward
Loser66
  • Loser66
\(csc \theta =\dfrac{1}{sin\theta}\\cot \theta=\dfrac{cos\theta}{sin\theta}\) hence \(csc(\theta)-cot(\theta)= \dfrac{1}{sin(\theta)}-\dfrac{cos(\theta)}{sin(\theta)}=\dfrac{1-cos(\theta)}{sin(\theta)}=\dfrac{1}{2}\)
Loser66
  • Loser66
Now, restrict the solution from 0, since if \(\theta =0\) , then \(sin(\theta )=0\), that make the expression undefined.
Loser66
  • Loser66
we have: \(2(1-cos(\theta))= sin(\theta)\) square both sides and solve for \(cos (\theta)\)

Looking for something else?

Not the answer you are looking for? Search for more explanations.